Three Years in the "Bloody Eleventh" : The Campaigns of a Pennsylvania Reserves Regiment - Gibbs, Joseph, 1965- (Book collections on Project MUSE., 2002)
Hailing from the Keystone State's rugged western counties, the Eleventh Pennsylvania Reserves was one of the Civil War's most heavily engaged units. Of more than 2,100 regiments raised by the North, it suffered the eighth highest number of battle deaths, earning it the gruesome sobriquet "Bloody Eleventh." Three Years in the "Bloody Eleventh" tells the story of this often-overlooked element of the Army of the Potomac from before the war up through 1864. Drawing on letters, diaries, and archival documents, Joseph Gibbs writes of men such as Colonel Thomas Gallagher, who led his troops into battle smoking a cigar, and Samuel Jackson, who became the regiment's commander following Gallagher's promotion. He rediscovers the complexities of the men who commanded the brigades and divisions of which the Eleventh Reserves was a part-figures such as George Meade, John Reynolds, and Samuel Crawford. While Gibbs writes about the officers, he never loses sight of the men in the ranks who marched into places such as Gaines' Mill, Miller's Cornfield at Antietam, and the Wheatfield at Gettysburg. Nor does he forget the homes, wives, and children they left behind in western Pennsylvania. With its meticulous research and lucid prose, Three Years in the "Bloody Eleventh" provides both scholars and Civil War enthusiasts with an unprecedented look inside the trials and tribulations of one of the war's most battle-tested units.